How should breeders react when aided by helpers? - Carranza, Juan; Polo, Vicente; Valencia-Ruíz, Juliána; Mateos, Concha; de la Cruz, Carlos (Elsevier, 2008)
In cooperatively breeding systems, breeders may reduce their provisioning to the brood when aided by helpers. However, this is found in only some species, and the reasons for the different reactions of breeders are far from clear. Recently, a paradoxical case of breeders in the azure-winged magpie, Cyanopica cyanus, increasing their contribution when aided by helpers has further complicated the issue. Existing models on the response of breeders consider only whether helpers contribute to increase the amount of food delivered to the brood. Helpers, however, can also contribute with other types of help that may increase the value of the whole brood for parents, such as reducing predation rate. Here we present a deterministic decision-making model to predict how parents should reduce or increase their parental effort on the basis of the relative role of both types of helpers’ contributions: delivering food and/or dispensing protection against predation. The model can be used by field workers to make qualitative and quantitative predictions with their data. As an example, we show how data for the azure-winged magpie predicts the observed increase of parental contribution in the presence of helpers.
Keywords: Animales - Hábitos y conducta; azure-winged magpie; cooperative breeding; Cyanopica cyanus; helpers; optimal investment; parental care; provisioning